2005
DOI: 10.1210/me.2004-0336
|View full text |Cite
|
Sign up to set email alerts
|

Direct Regulation of HOXA10 by 1,25-(OH)2D3in Human Myelomonocytic Cells and Human Endometrial Stromal Cells

Abstract: Vitamin D receptor (VDR) and the functionally active form of its ligand, 1,25-(OH)2D3, have been implicated in female reproduction function and myeloid leukemic cell differentiation. HOXA10 is necessary for embryo implantation and fertility, as well as hematopoeitic development. In this study, we identified a direct role of vitamin D in the regulation of HOXA10 in primary human endometrial stromal cells, the human endometrial stromal cell line (HESC), and in the human myelomonocytic cell line, U937. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 72 publications
2
89
0
11
Order By: Relevance
“…Indeed, in vitro exposure of endometrial cells to vitamin D has been shown to modulate the expression of factors that are appreciated to impact on endometrial receptivity [43][44][45], thus supporting our conjecture. Consistent with our hypothesis, higher midyear UVB intensity was identified as an independent and positive predictor of fresh ET related LBR's (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, in vitro exposure of endometrial cells to vitamin D has been shown to modulate the expression of factors that are appreciated to impact on endometrial receptivity [43][44][45], thus supporting our conjecture. Consistent with our hypothesis, higher midyear UVB intensity was identified as an independent and positive predictor of fresh ET related LBR's (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…The delineated changes in 25-hydroxylating capacity along the endometrial cycle, while CYP27B1 expression remains constant, 22 suggest that local 25(OH)D synthesis could be more relevant than 1,25D production for VDR control of NE cyclic growth. Therefore, customizing VD supplementation strategies throughout the endometrial cycle to achieve an appropriate local 25(OH)D production should improve 1,25D/VDR autocrine/paracrine regulation of genes controlling Th1/Th2 responses toward tolerance 37,44 in endometriosis, or the increases in the HOXA10 gene, 45,46 required to correct abnormalities in fertility due to embryo implantations defects. The direct correlation existing between the increases in 25-hydroxylating enzymes and CYP24A1 induction, the enzyme degrading the excess of active VD metabolites, also suggest that the NE mimics the systemic VD endocrine system in its tight self-regulation for protection against VD toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mineralisation of fetal bones occurs relatively late in pregnancy, while the induction of VDR and CYP27B1 in both maternal and fetal placental tissues occurs early in gestation, and thus alternative actions for intracrine 1,25(OH) 2 D have to be taken into consideration now (Evans et al 2004). These include possible effects on fetal development through homeobox gene expression (Du et al 2005) and placental vascularisation (Woodham et al 2011). Studies by ourselves and others have supported an immunomodulatory function for vitamin D within the placenta and the specific role of maternal decidua in this process becomes the major focus of the current review.…”
Section: Vitamin D and Human Pregnancymentioning
confidence: 99%